2021
DOI: 10.3390/cancers13225708
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Circular RNA-102450: Development of a Novel Diagnostic Procedure for Lymph Node Metastasis from Oral Cancer

Abstract: Circular RNAs (circRNAs), which form as covalently closed loop structures, have several biological functions such as regulation of cellular behavior by adsorbing microRNAs. However, there is limited information of circRNAs in oral squamous cell carcinoma (OSCC). Here, we aimed to elucidate the roles of aberrantly expressed circRNAs in OSCC. CircRNA microarray showed that circRNA-102450 was down-regulated in OSCC cells. Clinical validation of circRNA-102450 was performed using highly sensitive droplet digital P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Therefore, novel therapeutic targets for OSCC that act at a molecular level are needed. Numerous endogenous circRNAs are gaining increasing attention in cancers [ 13 , 33 , 34 , 35 ]. Several reports [ 13 , 33 , 34 , 35 ], including our previous study [ 13 ], showed that circRNAs are involved in the progression, metastasis, and multidrug resistance of cancers, suggesting that circRNAs could be diagnostic and/or therapeutic targets for multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, novel therapeutic targets for OSCC that act at a molecular level are needed. Numerous endogenous circRNAs are gaining increasing attention in cancers [ 13 , 33 , 34 , 35 ]. Several reports [ 13 , 33 , 34 , 35 ], including our previous study [ 13 ], showed that circRNAs are involved in the progression, metastasis, and multidrug resistance of cancers, suggesting that circRNAs could be diagnostic and/or therapeutic targets for multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The loop structures of circRNAs confer stability and resistance to endonuclease-mediated degradation that in turn affords substantially longer circulatory half-lives relative to linear RNAs [ 12 ]. Endogenous circRNAs contain selectively conserved miR binding sites and thereby can function as efficient miR sponges that counteract miR activity [ 12 , 13 , 14 , 15 ]. Although recent research on circRNAs provided promising new insights into miR regulation [ 12 , 15 ], the construction and application of artificial synthetic circRNAs targeting specific onco-miRs remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…More and more research has displayed the vital roles of circRNAs in tumorigenesis and advancement, including OSCC 9 . For instance, circ‐102,450 exerts a repressive effect on OSCC cell invasion and proliferation 10 . Also, circ‐IGHG 11 and circ‐EPSTI1 12 contribute to OSCC progression through inducing epithelial‐to‐mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…9 For instance, circ-102,450 exerts a repressive effect on OSCC cell invasion and proliferation. 10 Also, circ-IGHG 11 and circ-EPSTI1 12 contribute to OSCC progression through inducing epithelial-to-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…Le et al comprehensively summarized and introduced various types of non-coding RNAs and their clinical applications in lung cancer [ 17 ]. Furthermore, the significant role of recently highlighted non-coding RNAs, including small nucleolar RNAs (snoRNAs) and circular RNAs (circRNAs), were investigated in breast cancer and oral cancer [ 18 , 19 ]. In addition, it is shown in this Special Issue that not only non-coding RNAs but also coding RNAs, including NOTCH1 mRNA, are notable prognostic markers in head and neck squamous cell carcinoma (HNSCC) [ 20 ].…”
mentioning
confidence: 99%